Behavioral Problems in Children Patient with Epilepsy in RSUD Dr. Moewardi Surakarta - Budiati, Rachmania; ., Mustarsid; ., Sumardiyono (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2015)
Background: Epilepsy is a chronic neurological disorder impacting on the child development. Children with epilepsy are at considerable risk for behavioral problems such as hyperactivity disorder, emotionality, and conduct problems. Comprehensive care including assessment of behavioral problems is needed for epileptic children. This study aimed to determine the differences in behavioral problems in children patient with epilepsy compared with children patients without epilepsy. Methods: The cross sectional study was conducted by 36 patients which consist of 20 children with epilepsy and 16 children without epilepsy in the pediatric clinic of RSUD Dr. Moewardi who met the inclusion criteria. Behavioral problems were screened by using the Strength and Difficulty Questionnaire (SDQ) Indonesian version. Data were analyzed by Fisherâs test and binary logistic regression. Results: Groups of children with epilepsy were significantly higher experiencing behavioral problems (36,1% vs 2,8% in controls, p < 0.001). Significant differences were also found in the percentage of emotional disorders and hyperactivity (p = 0.018 dan p = 0.004). Based on the multivariate analysis using binary logistic regression we concluded that the factors associated with behavioral disorders in children with epilepsy were the presence of a focus on EEG (95% CI 1.68â238.63, p = 0.018) and AEDâs polytherapy (95% CI 1.03-67.14, p = 0.046). We also found that the presence of a focus on EEG was a factor related to hyperactivity (95% CI 1.75-141.40, p = 0.014). Conclusions: Children patient with epilepsy have at greater risk behavioral problems than children without epilepsy. A focus on the result of EEGÂ and AEDâs polytherapy are factors associated with increased risk of behavior problems in children with epilepsy. Keywords: epilepsy, children, behavioral problems, SDQÂ